Predicting binge drinking among university students: Application of integrated behavioral model. - Hordofa Gutema; Yamrot Debela; Bizuayehu Walle; Kidist Reba; Tebkew Shibabaw; Tolera Disasa (PLoS ONE)
Background Binge drinking is a pattern of harmful use of alcohol and it is defined as four drinks for women and five drinks for men in about 2 hours. This behavior causes public health problems like damaging different body organs. Objective To assess binge drinking and associated factors among Bahir Dar University students in Northwest Ethiopia. Method A cross sectional study was conducted in November 2017. Systematic sampling technique was used to select 422 participants. Structured questionnaire was used to collect data. Linear and Logistic regression models were used to predict the role of explanatory variables on behavioral intention and binge drinking, respectively. Independent variables with a p-value of <0.05 at 95% confidence interval were considered as statistically significant in the final model. Result A total of 413 students participated in this study and 33.4%(95% CI: 28.3-38.9) were engaged in binge drinking. Experiential attitude, instrumental attitude, and self-efficacy were found to be significant predictors of intention to binge drinking (p<0.05). Experiential attitude, environmental constraint, injunctive norm, and knowledge predictors were significantly associated with binge drinking (p<0.05). Conclusion Our study indicated that one-third of the students practiced binge drinking. This behavior was associated with experiential attitude, injunctive norm, environmental constraints, and knowledge factors. Additionally, experiential attitude, instrumental attitude, and self-efficacy constructs had explained behavioral intention. This implies focusing on the abovementioned determinant factors is imperative while designing intervention strategy.